2021
DOI: 10.52296/vje.2021.94
|View full text |Cite
|
Sign up to set email alerts
|

Social resources mobilization for general education development: A case study for secondary schools in Ho Chi Minh city, Vietnam

Abstract: The mobilization of social resources for educational development in schools is considered an important demonstration of the roles and responsibilities of parents and the community for the cause of education. This paper describes the frequency and efficiency of nine categories of social resources mobilization used in secondary schools in the South of Vietnam. The research team identified the reasons for and methods by which the mobilization of social resources takes place in six secondary schools in Southern Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A. papayae has been successfully used as biocontrol agent in different regions around the world [36,37]. Our findings indicate a potential new addition to the list of parasitoid wasp species which attack P. marginatus in Vietnam [16,24,27,[30][31][32]. However, the abundance of these parasitoids was not efficient for the biocontrol of P. marginatus [43].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A. papayae has been successfully used as biocontrol agent in different regions around the world [36,37]. Our findings indicate a potential new addition to the list of parasitoid wasp species which attack P. marginatus in Vietnam [16,24,27,[30][31][32]. However, the abundance of these parasitoids was not efficient for the biocontrol of P. marginatus [43].…”
Section: Discussionmentioning
confidence: 92%
“…Acerophagus papayae Noyes and Schauff, Anagyrus loecki Noyes and Menezes, and Pseudleptomastix mexicana Noyes and Schauff (Hymenoptera: Encyrtidae) were regularly introduced to control P. marginatus, especially in Guam, Palau, Florida and Hawaii (USA), India, and Sri Lanka [22,24,28,29]. Among the parasitoid wasps, A. papayae (Hymenoptera: Encyrtidae) is one of the most effective species in controlling P. marginatus [30][31][32][33]. Mastoi et al [34] reported on the natural enemies of P. marginatus in the Malaysian Peninsula, and observed A. papayae to be a parasitoid wasp on this mealybug.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric composites reinforced with natural fibers are used in many applications at the moment. A study that aims to determine the visco/elastic constants of these materials is presented in [53]. Natural fibers have viscoelastic behavior and superior specific properties.…”
Section: Introductionmentioning
confidence: 99%
“…and equipment. In addition, according to Nguyen and Nguyen (2021) state that the role of the construction industry can mobilize the use of human and material resources in the development of the housing and infrastructure sector that can create jobs and increase economic efficiency. The construction industry produces output from the construction industry that is inseparable from national output, which is part of the Gross Domestic Product (GDP) in both developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%